Exploring strategic execution: A case study on the use of the balanced scorecard within an Irish hospital. Issue 4 (21st November 2016) - Smith, Meabh; Loonam, John
Abstract : Purpose: Globally and particularly in Ireland, reduced expenditure on healthcare along with increasing pressure to increase patient throughput and improved performance against standards, is forcing healthcare providers to adopt tools from the business sector and apply them in the healthcare sector to bring about improved performance. The paper aims to discuss these issues. Design/methodology/approach: This study is interpretivist in nature, specifically focussing on exploring how the balanced scorecard can support improved service delivery within a hospital department. The research will conduct an exploratory case study of a single hospital site within the Irish republic. This research is based on qualitative interviews with corroboration from document review and direct observation. This study provides a snap-shot of the Cath Lab service at a moment in time. Findings: The development of a strategy map and proposed balanced scorecard for an Irish hospital unit. Originality/value: The development of a balanced scorecard for a healthcare organisation.